(untitled) (Eurasian Journal of Philology Science and Education, 2018)
The use of the Latin alphabet is an important necessity, affecting almost all the vital areas of statehood. Formation of the Kazakh script is a complex and multifaceted process. Historical and political events had a tremendous impact on the formation of the language environment and ways of their written reflection. The Specificity of pronunciation of some elements of the Kazakh sound-range complicated the choice of a certain alphabet, which became one of the reasons for changing the graphics over the centuries. The use of Arabic, Latin, and Slavic graphics was a search, conjugated by disputes between scientists and eminent personalities of the Kazakh people. Due to the demands of the times, as well as the development of a multilingual environment for the younger generation with the study of a number of disciplines in English was made a general decision to choose the Latin alphabet. This article discusses the key problems associated with this process.